2003
DOI: 10.1086/378662
|View full text |Cite
|
Sign up to set email alerts
|

Gymnosperms from the Middle Triassic of Antarctica: The First Structurally Preserved Cycad Pollen Cone

Abstract: The first permineralized cycad pollen cone is described from the lower Middle Triassic of Antarctica. The cone is characterized by helically arranged, wedge-shaped microsporophylls, each with five or more spinelike projections extending from the rhomboid distal face. The vascular cylinder is dissected and produces paired traces to each microsporophyll. Three vascular bundles enter the base of the microsporophyll and divide to produce at least five vascular strands in the sporophyll lamina. Pollen sacs occur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Superficially, this array of cells is similar to those of the pollen sac wall in the cycad Delemaya spinulosa from the Middle Triassic of Antarctica (cf. Klavins et al 2003, fig. 3D), and the outer pollen sac wall of some modern cycads (Lang 1897).…”
Section: Plantsmentioning
confidence: 99%
“…Superficially, this array of cells is similar to those of the pollen sac wall in the cycad Delemaya spinulosa from the Middle Triassic of Antarctica (cf. Klavins et al 2003, fig. 3D), and the outer pollen sac wall of some modern cycads (Lang 1897).…”
Section: Plantsmentioning
confidence: 99%
“…There are also a number of insects that are parasitic on cycads although not known to be involved in pollination, especially lepidopterans; however, the earliest undisputed lepidopteran fossils do not appear until the Jurassic (Norstog and Nicholls, 1997;Grimaldi and Engel, 2005). Klavins et al (2003Klavins et al ( , 2005 also reported coprolites in isolated cycad pollen sacs that occur in association with the microsporangiate cone Delemaya Klavins, Taylor, Krings, et Taylor, the only other cycad taxon known from the Triassic of Antarctica and possibly representing the pollen cone of Antarcticycas, although the two taxa have not yet been found in attachment. The coprolites in pollen sacs associated with Delemaya are composed entirely of pollen (Klavins et al, 2003(Klavins et al, , 2005, whereas those in the Antarcticycas cataphylls are not.…”
Section: May 2006]mentioning
confidence: 99%
“…Klavins et al (2003Klavins et al ( , 2005 also reported coprolites in isolated cycad pollen sacs that occur in association with the microsporangiate cone Delemaya Klavins, Taylor, Krings, et Taylor, the only other cycad taxon known from the Triassic of Antarctica and possibly representing the pollen cone of Antarcticycas, although the two taxa have not yet been found in attachment. The coprolites in pollen sacs associated with Delemaya are composed entirely of pollen (Klavins et al, 2003(Klavins et al, , 2005, whereas those in the Antarcticycas cataphylls are not. In extant cycads, some pollinating insects consume pollen and some do not (Norstog and Nicholls, 1997;Stevenson et al, 1998), so the composition of the coprolites does not necessarily shed light on the ecological relationship of the insects feeding on the cataphylls to Antarcticycas.…”
Section: May 2006]mentioning
confidence: 99%
“…The group appeared in the Triassic and has survived until nowadays (Taylor et al 2009). Currently avai la ble data show that the elongated perpendicular alveolae of the ectexine, which are so characteristic of pollen of mo dern cycads, existed at least as early as in the Jurassic (Za vialova & Van Konijnenburgvan Cittert, submitted), or, perhaps, even earlier (Klavins et al 2003). This seems to be the case of evolutionary stability.…”
Section: Discussionmentioning
confidence: 98%